Pertumbuhan benih ikan mas, Cyprinus carpio, yang diberi pakan dengan dosis dan frekuensi berbeda - Biduan, Tinus O O.; Salindeho, Indra R. N.; Sambali, Hariyani (Universitas Sam Ratulangi, 2020)
The objectives of this research were to find out the optimum dose and frequency of feeding regime to ensure the maximum growth of carp-seeds, Cyprinus carpio, reared in the backyard pond with recirculation system. The experiment was carried out in 2x3 factorial experimental design and the experimental units were designed in randomized block. Two factors were tested in this experiment; the first factor, dose of feeding, had three levels, 3%, 4% and 5% of the total body weight per day; and the second factor had 2 levels, 2 and 3 times per day. Hence there were 6 treatments were applied, and each treatment was triplicated. Each repetition represented group of fish with different weight. There were 18 experimental units, and each experimental unit was composed of 8 tested fish, therefore there were 144 tested fish, which were weighed at the beginning of the experiment and then every week during the 6 weeks period of the experiment. The weight data were converted into FCR, absolute, relative and daily growth rate, and were statistically analyzed using JMP statistic-program (SAS-institute). The results showed the absolute growth of fish at dose of 3% was significantly lower than that of fish at the dose of 4% and 5%, which was not significantly different. The relative and daily growth rate was not significantly affected by the different dose of feeding regime. There was no significant difference in FCR, absolute, relative and daily growth rate between fish fed 2 and 3 times per day. The best FCR, 1,46, was performed by fish fed 3% of the body weight per day, and this value was significantly different with that of the fish fed 4% or 5%. The results of this experiment suggest that, carp reared in backyard pond with recirculation system should be fed twice a day, with a dose of 3% of the body weight each day.